Changes of blood flow velocity indicating mechanical compression of the vertebral arteries during rotation of the head in the normal human measured with transcranial Doppler sonography - Sandro Rossiti; Reinhard Volkmann (Arquivos de Neuro-Psiquiatria)
The dynamical changes of blood flow velocity of the intracranial vertebral arteries (VA's) and proximal basilar artery (BA) provoked by rotation of the head in normal volunteers were measured using pulsed-wave transcranial Doppler sonography (TCD). In another group both VA's were examined simultaneously with 2-channel TCD. Blood flow velocities diminished compared to the neutral position in all vessels, independently of die side. Total obstruction of the flow was not observed. Our findings reveal a definitive decrease of blood flow velocity at the vertebrobasilar artery system provoked by rotation of the head in normal humans. This physiological phenomenon is suggested to have an impact on the cerebral blood flow in patients with impaired autoregulation of the cerebral vessels, low volume flow reserve in the contralateral VA or insufficient collateral channels because of normal anatomical variation, especially those patients under general anesthesia or comatose.